Constraints to Community Participation in Tourism In Kenya: The Mwaluganje Elephant Sanctuary (The Gaze: Journal of Tourism and Hospitality, 2021)
Community Based Tourism (CBT) is among several types of tourism that have been considered sustainable and beneficial to the host populations in conservation areas. The local community participation in tourism in conservation areas is supposed to be high and its members should benefit from the tourism process. However, having been presented with opportunity to improve their livelihoods, communities are constrained in various ways and generally fail to benefit from tourism development. This study was set to investigate constraints to community participation in conservation areas. It was carried out in Mwaluganje Elephant Sanctuary (MES) in Kwale County, Kenya, using a descriptive survey design. Data was collected using researcher administered questionnaires and oral interviews. The results indicated that lack of coordination among stakeholders; inadequate financial resources, lack of conducive environment for tourism growth, and lack of skills/knowledge were major constraints to participation. The study concludes that to address both operational and structural constraints to community participation, the national and county governments should develop policies that compel investors to honour agreements with communities, assist communities to enter into fair collaborations with investors, and provide incentives to investors in tourism.